Ultrasonic treatment with nickel electroplating combined with oxidation for developing γ-Al2O3 washcoat on Fe-Cr-Al substrate - Firdianto, Ade (2012)
Fe-Cr-Al is used as metallic support for catalytic converter due to its high thermal conductivity, lower heat capacity, high temperature and mechanical shock resistance. γ-Al2O3 is the most widely used material as washcoat which embedded on metallic support for the catalytic converter application. The problem is the coating adhesion between the metallic support and the ceramic washcoat becomes a problem in longterm high temperature oxidation. On the other hand, the gamma phase of alumina will be transformed to alpha phase at high temperature. The ultrasonic technique via cavitation bubbles and high velocity can make surface deformation and also accelerate the γ-Al2O3 powders to bombardment occurred on the Fe-Cr-Al surface. This process generates sufficiently heat and γ-Al2O3 layer can be formed on the FeCr-Al surface. Subsequently, electroplating process embeds the nickel and also can strengthen the adhesion when oxidized. Therefore, this work presents the ultrasonic treatment with nickel electroplating for developing γ-Al2O3 washcoat on Fe-Cr-Al substrate and oxidation treatment for catalytic converter application. Washcoat layer on Fe-Cr-Al was prepared by using γ-Al2O3 powders through ultrasonic treatment. Catalyst material was prepared by using nickel electroplating. The oxidation kinetics was conducted at temperatures of 500, 700, 900 and 1100 oC in air for 100 hours. The surface morphology, cross section analysis, chemical composition, elemental maps and phase structure of coated Fe-Cr-Al were analyzed by Scanning Electron Microscope (SEM), Energy Dispersive X-ray Spectroscopy (EDS) and X-ray Diffraction (XRD) respectively. The results showed that the surface of Fe-Cr-Al contained γ-Al2O3 powders after ultrasonic treatment. The layer of alumina oxide has been formed on coated Fe-Cr-Al and no spallation occurred after oxidation. It is prove that γ-Al2O3 washcoat and NiO as a catalyst have successfully embedded on Fe-Cr-Al substrate by ultrasonic treatment combined with nickel electroplating at long term high temperature oxidation that enhance the adhesive properly.